Lenaion, Ikria, and the Old Agora - Theatrical Spaces in Archaic Athens - Lindner, Gyula (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
The research of recent decades has made the topography of archaic Athens increasingly clear. However, there are some questions in the 7th/6th century cityscape that even the ongoing excavations cannot aswer. One such unclear point concerns the theatrical spaces used before the construction of the Dionysos Theatre: it is not clear where the sanctuary area called Lenaion, or the orchestra and ikria mentioned by the lexicographers were located. It is also unclear whether in Athens, besides the theatre on the southern slope of the Acropolis, there were other venues for theatrical performances and choral competitions. The study examines the above issues in the context of the topographical problems of archaic Athens through the available literary, archaeological and epigraphic sources.